Influência de bordas naturais e antrópicas na estruturação filogenética de comunidades arbóreas no sul de Minas Gerais - Torres, Daniel Mendonça (2018)
The present work aimed at analyzing the influence of natural and anthropic edges on the phylogenetic structure of forest tree communities in a fragmented landscape in southern Minas Gerais. The hypotheses tested were: (1) tree communities present variation in the phylogenetic structure between natural and anthropic edges; and (2) natural edges by edaphic heterogeneity present phylogenetic structure different from alluvial natural edges and also in relation to anthropic edges. The results demonstrated that different edge origins influenced the phylogenetic structuring of forest tree communities in southern Minas Gerais. In natural edges, there was a tendency of phylogenetic clustering in relation to the phylogenetic overdispersion in the anthropic edges. The more pronounced clustered structure at the alluvial edges might be shaped by environmental filters. However, the floristic richness and ecology of these edge environments, with different histories of perturbation and successional stochasticity, suggest that the phylogenetic analyzes of these phytophysiognomies through functional diversity descriptors will allow better predictions about the processes involved in the organization of these communities. The relationships found between spatial variables and diversity metrics showed that the distance of continuous forests and the size of the fragment also influenced the phylogenetic structure of tree communities in the southeast province of the Atlantic Forest. Finally, we identified the trend of greater phylogenetic diversity in the smaller fragments, suggesting that all the remnants of the Atlantic Forest, from the continuous forests to the small fragments, are relevant for its conservation.